The Effect of Customer-Based Brand Equity (CBBE) BPJS ketenagakerjaan after the simultaneous implementation of the re-call strategy on informal worker (BPU) purchase intention - Pradana, Bangkit; Irawan, Enjang Pera (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indonesia's growing population demands social protection, such as health insurance and pension insurance. Although BPJS Ketenagakerjaan strives to improve services, challenges to social protection still exist, especially for informal workers. Further efforts are needed to increase their participation in social security programs. This study aims to investigate the effect of Customer-Based Brand Equity (CBBE) BPJS Ketenagakerjaan after the simultaneous implementation of the Re-Call strategy on Non-Wage Earner (BPU) Purchase Intention. The growth of the labour force in Indonesia raises the complexity of the economy and the high risk of workplace accidents. BPJS Ketenagakerjaan exists as an effort by the government to provide social protection to workers, including informal workers. The Re-Call strategy is carried out to increase the participation of informal workers in the BPU Program. This study proposes a hypothesis that CBBE BPJS Ketenagakerjaan through the Re-Call strategy has a positive effect on BPU's Purchase Intention. The Structural Equation Modelling (SEM) analysis method was used to analyse survey data collected from 400 active participants of BPJS Ketenagakerjaan BPU. The results showed that there was a positive and significant influence between CBBE BPJS Ketenagakerjaan and BPU Purchase Intention. These findings make an important contribution in understanding the dynamics of the relationship between CBBE elements and consumer purchase interest, as well as their implications for increasing informal workers' participation in social security programs.